TECHNOLOGY OF SUPERCONDUCTING MATERIALS - Giunchi, Giovanni; Bekmirzaev , Rahmatillo; Nabiev, Bahodir (Физико-технологического образование, 2021)
The present superconducting materials find hard hurdles to find applications for the real life, mainly due to the cryogenic issues. Waiting for future room temperature superconductors, the low temperature of the present materials is a condition that limits a lot the applications in the real life. The liquid He and the liquid N2, used to cool down the LTS materials, impose severe conditions to perform safely their containment and their transfer. The present worldwide use of superconducting magnets are for the human diagnostics with MRI magnets and the chemical analysis with NMR Magnets.